ANALISIS TERJEMAHAN LIRIK LAGU BERBAHASA INDONESIA KE DALAM BAHASA JEPANG OLEH HIROAKI KATO - Putri, Annisa; Hermandra, Hermandra; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research describe the translation technique and method whichapplied on translating Hiroaki Kato’s song lyrics from Indonesia language to Japanlanguage and the translation equivalence of it in 2018. The songs are Jauh di Mata dekatdi Hati, Meraih Bintang dan Bright As The Sun. The theories used in this research are translation technique according to Molina and Albir (2002), translation method according to Newmark (1998) and equivalence translation according to Nida and Taber (1982) .The data were analyzed with qualitative-distibutive method. Data analysisc tehcnique used in this research are literature study method and documentation technique The results of this research show that from 44 translation unit, 3 datas are borrowing, 1 data is description, 1 data is compensation, 4 datas are particularization, 26 datas aremodulation and 9 datas are transpotition. While the orientation of the translation method is the target language and dynamic equivalence as the translation equivalence.Key Words: Translation, Technique, Method, Equivalence